Enhancing Revenue and Customer Satisfaction Through Effective Hotel Bar Management - Saputra, Rolando Lorenza; Wijoyo, Adhistyo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the optimal ways for effectively operating hotel bars with the goal of maximizing revenue and improving customer satisfaction. The study used a combination of qualitative and quantitative methods, focusing specifically on significant issues such as personnel training, inventory control, menu development, and incorporation of technology. Surveys generate numerical data, while interviews offer subjective insights, combining to create a comprehensive understanding of these issues. The results suggest that the presence of proficient staff, efficient inventory management systems, creative menu choices, and modern technological resources significantly improve operational efficiency and consumer satisfaction. Nevertheless, further investigation is necessary to examine the enduring impact on customer loyalty and profitability, as well as to address the challenges associated with adopting technology in different hotel environments. The aim of this research is to offer hotel managers practical recommendations for enhancing their bar operations, resulting in the establishment of remarkable guest experiences and sustainable revenue growth